2013
DOI: 10.1097/bot.0b013e318269ba8e
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Displaced Fractures of the Lateral Condyle of the Humerus Treated Using High Strength, Bioactive, Bioresorbable F-u-HA/PLLA Pins

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…There has been some study into the popular topic of using bioresorbable implants, which could potentially solve this problem. A study of eight patients by Takada et al [15] showed no skin erosion and no infections in the use of bioresorbable F-u-HA/PLLA pins. The pin can be trimmed flush as it does not require to be left proud for removal, and therefore, the risk of erosion is reduced.…”
Section: Discussionmentioning
confidence: 97%
“…There has been some study into the popular topic of using bioresorbable implants, which could potentially solve this problem. A study of eight patients by Takada et al [15] showed no skin erosion and no infections in the use of bioresorbable F-u-HA/PLLA pins. The pin can be trimmed flush as it does not require to be left proud for removal, and therefore, the risk of erosion is reduced.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding osteoconduction, numerous studies using rabbit models have demonstrated the osteoconductive ability and bone bonding features of u-HA/PLLA [7,8,9]. Thus, u-HA/PLLA is used extensively as bone plates and screws for osteosynthesis in different surgical specialties such as orthopedics, plastic surgery, or thoracic surgery [10,11,12,13]. However, these animal experiments only tested the osteoconductive ability of u-HA/PLLA using a rod inserted fully into the knee, such that there was full bone contact.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable implants have been applied for various pediatric orthopaedic fixation without the need for routine implant removal as is performed for metallic hardware [9] , [10] , [11] . Implants made of F-u-HA/PLLA have advantages over PLLA-only implants, including: expectation of greater initial mechanical strength [9] , implant radio-opacity enables radiographic observation during healing, good biocompatibility throughout the resorption process, and direct binding to surrounding bone without intervention involving fibrous tissue [10] . F-u-HA/PLLA implants may cause foreign body reactions associated with PLLA releasement.…”
Section: Discussionmentioning
confidence: 99%